KOMPOSISI ODONATA DI KABUPATEN BANGKA SELATAN - Fadilatul Fitria; Nur Annis Hidayati; Ade Yusni Pranata; Herry Marta Saputra; Budi Afriyansyah (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2019)
The existence and diversity Odonata in an area could reflect the quality of a habitat's environment such as pH, temperature, light intensity, conditions of chemical and availability of water and foods. The purpose of this study was to record the composition Odonata in Regency of Southern Bangka. This research was conducted in two habitats namely natural in the form of rivers and artificial in the form of tin mining lakes in Regency of Southern Bangka. The method used was the transect line with a transect length of 100 m. Odonata was captured using an insect net then the number of species is recorded. Abiotic factors measured include temperature, light intensity and pH of water. Result showed that 1,166 individuals Odonata that were found at the study site consisted of 18 species which belong to four family and two suborder. Both the species number and individual found anound the river was greater then the tin mining lake. The highest number of species found in the river was 17 and the lowest found tin mining lake was 10. The highest number of individuals found in the river was 694 and the lowest found tin mining lake was 472. The highest diversity indices was at Sebagin river (2.20) and the highest evenness indices was at Nyelanding tin mining lake (0.9639).